New Distributional Record of Twelve Scleractinian Corals From Saint Martin’s Island, Bangladesh (Bangladesh Journal of Zoology, 2021)
Saint Martin's Island is the only island in Bangladesh where coral communities are found. An expedition on marine biodiversity monitoring of Saint Martin’s Island through underwater visual census method was carried out from December 2017 to March 2018. In this study, a total of 25 scleractinian coral species of 8 families and 14 genera were identified, of which 12 species, Dipsastraea lizardensis, Dipsastraea maritima, Dipsastraea veroni, Favites acuticollis, Favites melicerum, Favites pentagona, Goniastrea stelligera, Goniopora albiconus, Goniopora norfolkensis, Pavona clavus, Plesiastrea versipora, and Psammocora exesa were recorded for the first time in Bangladeshi marine water. These new records exemplify gaps in sampling and recording of coral species in Bangladesh, and suggest the need of extensive research on coral ecosystem in the country. Assessment of different valid reports and publications including the present study revealed that a total of 98 species of hard corals of 18 families and 37 genera have been reported until now in Saint Martin’s Island as well as Bangladesh.Bangladesh J. Zool. 49(1): 03-18, 2021